Longevity of Mycobacterium bovis in brushtail possum (Trichosurus vulpecula) carcasses, and contact rates between possums and carcasses - Barron, MC; Pech, RP; Whitford, J; Yockney, IJ; de Lisle, GW; Nugent, G (New Zealand veterinary journal, 2011)
AIM: To determine, for a variety of environmental conditions, how long Mycobacterium bovis might remain viable inside the carcass of a brushtail possum (Trichosurus vulpecula) that died of bovine tuberculosis (Tb), and to measure the rate of contact between free-ranging possums and possum carcasses. METHODS: Lesions of M. bovis were simulated by inoculating excised spleens weighing 0.5-1 g with 0.2 mL liquid culture containing approximately 5 x 10 7 cfu M. bovis/mL. Simulated lesions were inserted into possum carcasses (n=48) at the peripheral lymph nodes. Carcasses were placed in the field at two sites (a tussock grassland and a podocarp-broadleaved forest site) and in two seasons (summer and winter) for up to 62 days. Survival rates of M. bovis were estimated by sampling the simulated lesions over time, and culturing the recovered lesion to determine if any viable M. bovis bacteria were present. The time taken for a free-ranging possum to first encounter a dead possum in its home range was estimated by live-trapping possums and fitting them with proximity loggers (n=13). A 'contact' was recorded if these possums came within 40-50 cm of proximity loggers fitted to possum carcasses. RESULTS: There were strong seasonal and site effects in the survival rate of M. bovis in possum carcasses. In the grassland habitat, no viable bacilli were cultured from any carcass after 3 days in summer, whereas in winter all samples were culture-positive for the first 20 days, and some were still positive after 27 days. The survival rates for forest habitat were intermediate between the results for grassland, and there were no culture-positive carcasses after 9 days in summer or 27 days in winter. In summer, infected carcasses (n=6) were first encountered by possums a mean 1.9 (range 0.4-6.7) days after placement. CONCLUSIONS: Possum carcasses were contacted by free-ranging possums within the period that viable M. bovis were shown to survive in a carcass. The risk of such infection is likely to be most significant in winter or in areas with microhabitats where the survival of M. bovis is high. However, the generally low survival rate of M. bovis in possum carcasses and the low frequency of possum-to-carcass contacts indicate this route of transmission alone could not maintain Tb in a possum population.